Rote-Meto comparative dictionary - Edwards, Owen (Asia-Pacific Linguistics., 2021)
This comparative dictionary provides an initial bottom-up reconstruction of one low-level Austronesian subgroup of the linguistic area of Wallacea: the Rote-Meto subgroup. This work forms one part of the larger bottom-up reconstruction of languages in this region, which is needed to fully understand the history of these languages.